Challenges of Implementing Rice Anchor Borrower Programme for Food Security in Kogi State, Nigeria - Yusuf, Ahmed Tijani; Yamma, Mohammed Abdullahi; Jacho, David S. (Kashere Journal of Politics and International Relations, 2025)
The smallholder rice farmers in Kogi State, Nigeria, are pivotal to national food security and economic stability, yet they face systemic challenges that undermine productivity, despite government policies targeting agricultural revitalization. The Diffusion of innovation theory was employed as theoretical framework and both primary and secondary methods were utilized. This study examines the interplay between federal and state agricultural rice policies—such as the Anchor Borrowers’ Programme (ABP) and the persistent obstacles confronting smallholder rice farmers in enhancing food security. Through qualitative review of policy documents and academic literature, the research identifies critical gaps in policy implementation, including dilapidated rural infrastructure and climate vulnerabilities. Findings reveal inefficient government policies in tackling the challenges of food security. The study underscores the urgent need for stakeholder-inclusive reforms and enhanced climate-resilient infrastructure to empower smallholder farmers. By addressing these challenges, policymakers can unlock Kogi State’s potential to contribute significantly to Nigeria’s rice self-sufficiency goals. While existing studies broadly address agricultural challenges in Nigeria, there is little focus on the unique socio-political and ecological dynamics of Kogi State. On this note, the study’s recommendations include effective government policies and localized policy design that enhances food security.